Assessing the content of a synthetic cannabinoid "research chemical" package. (29th March 2019) - Luzio, Ana; Couceiro, Joana; Ferreira, Carla; Quintas, Alexandre
Abstract : Introduction: Over the past several years, a new class of psychoactive substances has emerged from the drug market.[1–3 ] These Novel Psychoactive Substances (NPS) are defined as "a new narcotic or psychotropic drug, in pure form or in preparation, that is not controlled by the United Nations drug conventions, but which may pose a public health threat comparable to that posed by substances listed in these conventions" [1 ]. The largest and most popular group of NPS is Synthetic Cannabinoids (SC). SC are used as a 'legal' alternative to Cannabis, which means that they produce similar psychotropic effects to those of Δ 9 -THC. These substances are easily bought on internet shops and both blends or 'research chemicals' come in packets [2, 3 ]. These packets are advertised as containing a certain SC pure. Usually, pure substances from synthesis are very expensive. On contrary, SC 1g packets are sold for 10€ or less. In the present study, a SC called THJ-018 was bought in the internet as a 'research chemical' and its content was assessed by GC/MS and HPLC/DAD. Materials and methods: THJ-018 was bought as a 'research chemical' >99% purity. A gas chromatography system coupled with a mass selective detector and an automated injector were used for the analysis of the packet content. Helium was used as the carrier gas. For purification a HPLC system coupled with a photodiode array detector (DAD) and an autosampler, operated by Clarity software, was used with a reversed-phase column. The mobile phase was a solvent gradient system consisting of (A) 5% 10mM ammonia format and (B) 95% acetonitrile, optimized to achieve the best resolution. The chromatograms were recorded at λ = 320 nm. Results: Figure 1 shows the GC/MS chromatogram of methanol extract of THJ-018. It is clear from the chromatogram the presence of two peaks: THJ-018 (33, 072 min) and another compound (31, 952 min). Discussion and conclusions: The data gathered in this study shows that THJ-018 bought as a pure "research chemical" contains a significant amount of impurities. This suggests that SC bought online might not come in their pure state. According to Couceiro et al. [3 ], human cell lines exposed to JWH-018 (>99% pure), do not show a significant change on cell viability, pointing that this compound is not toxic as a standard. However, various effects resulting from an acute SC intoxication have been registered, such as cognitive deficits, agitation/violent behaviors, organ related problems, nausea/vomiting, seizures, anxiety, mydriasis, among others [2 ]. This might be pointing that substances sold online or at the streets do not come in a pure form and impurities are also part of the problems caused by NPS.